Investigations of work-life balance and stress for working women in the Indonesian banking sector - Eka Suhartini; Mahfud Nurnadjamuddin; Mapparenta; Suriyanti (Global Business & Finance Review (GBFR), 2023)
Purpose: Workloads have substantial impacts on the working woman's identity. The banking sector also exhibits this trend with long working hours, commuting, and potential job stress. This study investigates the possible relationships between work-family conflict, social support toward work-life balance, and job stress from Indonesian female bankers. Design/methodology/approach: This study obtains data from 197 female workers in the banking sector in I ndonesia and constructs a hypothesized path model by maximizing the covariance-based structural-equation modelling with the Lisrel 10.2 software. Findings: This study reports dynamic results as work-family conflict does not contribute to work-life balance but toward job stress. Furthermore, social support is foundational for the work-life balance but not toward stress. The partial mediating effect is also reported. Research limitations/implications: This study's predictive power can get further upgrades from a wider participant across the industry. The comparison between genders can clarify this issue's advantages and disadvantages. The social peers' positive support may remedy the work-life balance issue; thus, firms must recognize this problem at their managerial discretion. Originality/value: This study extends the neglected conjoint effects of work-family conflict and social support to work-life balance, decreasing job stress among working women. The novel finding suggests the absence of conflict in the family-office relationships, indicating that work-life balance requires an update on the office-level policy.
Keywords: 650; Women; Work-family conflict; Social support; Work-life balance; Job stress